Klasterisasi Jenis Musik Menggunakan Kombinasi Algoritma Neural Network, K-Means dan Particle Swarm Optimization - Alhaji Sheku Sankoh; Ahmad Reza Musthafa; Muhammad Imron Rosadi; Agus Zainal Arifin (Jurnal Buana Informatika, 2015)
Abstract. Having a number of audio files in a directory could result to unstructured arrangement of files. This will cause some difficulties for users in sorting a collection of audio files based on a particular category of music. In some previous studies, researchers used a method conducting to group documents on a web page. However, those studies were not carried out on file containing documents such as audio files; relatively they were conducted on files that contain text documents. In this study, we develop a method of grouping files using a combination of pre-processing approach, neural networks, k-means, and particle swarm optimization to obtain a form of audio file collections that are group based on the types of music. The result of this study is a system with improved method of grouping audio files based on the type of music. The pre-processing stage has therefore produced the best results on this approach based on spectrum analysis melody and bass guitar, which offers a value precision 95%, 100% recall and an F-Measure 97.44%.Keywords: Cluster, Music, NN, K-Means, PSOÂ Abstrak. Banyaknya file audio pada suatu direktori membuat sususan file tidak terstruktur. Hal ini akan menyulitkan pengguna untuk mengurutkan bahkan memilah kumpulan file audio berdasarkan kategori tertentu, khususnya kategori berdasarkan jenis musik. Pada penelitian sebelumnya, dilakukan pengelompokan dokumen pada suatu halaman website. Namun hal tersebut tidak dilakukan pada file selain dokumen, seperti file audio. Penelitian ini bertujuan untuk mengembangkan metode pengelompokan file berupa kombinasi pendekatan pre-processing, neural network, k-means, dan particle swarm optimization dengan masukan berupa file audio sehingga diperoleh keluaran berupa kumpulan file audio yang telah terkelompok berdasarkan jenis musik. Hasil dari penelitian ini yaitu berupa suatu sistem dengan pengembangan metode dalam pengelompokan file audio berdasarkan jenis musik. Metode pada tahap pre-processing memiliki hasil terbaik pada pendekatan berdasarkan analisa spectrum melodi gitar dan bass, di mana memiliki nilai precission 95%, recall 100% dan F-Measure 97,44%. Kata kunci: Klaster, Musik, NN, K-Means, PSO